2021
DOI: 10.3390/nano11020270
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and Immunotoxicity of Titanium Dioxide-Embedded Mesoporous Silica Nanoparticles (TiO2@MSN) in Primary Peripheral Human Blood Mononuclear Cells (PBMC)

Abstract: Background: TiO2 nanoparticles (TiO2 NPs) are the nanomaterial most produced as an ultraviolet (UV) filter. However, TiO2 is a semiconductor and, in nanoparticle size, is a strong photocatalyst, raising concerns about photomutagenesis. Mesoporous silica nanoparticles (MSN) were synthetized incorporating TiO2 NPs (TiO2@MSN) to develop a cosmetic UV filter. The aim of this study was to assess the toxicity of TiO2@MSN, compared with bare MSN and commercial TiO2 NPs, based on several biomarkers. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…In addition to all these environmental disturbance agents, sunscreen represents one of the principal sources of TiO2 and ZnO nanoparticles found in coastal environments (Schiavo et al, 2018 ) with high genotoxic potential (Di Giampaolo et al, 2021 ; Kukla et al, 2021 ). Thus, all the compounds mentioned above can contribute to the genotoxic effects observed in A. saxatilis erythrocytes collected in Porto de Galinhas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all these environmental disturbance agents, sunscreen represents one of the principal sources of TiO2 and ZnO nanoparticles found in coastal environments (Schiavo et al, 2018 ) with high genotoxic potential (Di Giampaolo et al, 2021 ; Kukla et al, 2021 ). Thus, all the compounds mentioned above can contribute to the genotoxic effects observed in A. saxatilis erythrocytes collected in Porto de Galinhas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use in medicine, titanium dioxide (TiO 2 ) NPs are used in food additives and cosmetics and have shown a significant immunotoxic potential [ 50 , 51 , 52 ]. A recent report on primary peripheral human blood mononuclear cells (PBMC) showed an altered redox state and cytokine release against TiO 2 NP exposure [ 53 ]. In this study, the embedding of mesoporous silica nanoparticles with TiO 2 NPs (TiO 2 @MSN) showed reduced induction of immune response, suggesting that this modification can adjust the NPs-induced immune response of TiO 2 NPs [ 53 ].…”
Section: Nanoparticles-induced Immunotoxicitymentioning
confidence: 99%
“…A recent report on primary peripheral human blood mononuclear cells (PBMC) showed an altered redox state and cytokine release against TiO 2 NP exposure [ 53 ]. In this study, the embedding of mesoporous silica nanoparticles with TiO 2 NPs (TiO 2 @MSN) showed reduced induction of immune response, suggesting that this modification can adjust the NPs-induced immune response of TiO 2 NPs [ 53 ]. BSA-functionalized TiO 2 NPs exposure to murine macrophage cells induced ROS generation, nitric oxide production, and antioxidants (e.g., SOD and Nrf2) depletion [ 54 ].…”
Section: Nanoparticles-induced Immunotoxicitymentioning
confidence: 99%
“…However, in HEK293T, the cell viability in the presence of both CuO@PEG NPs and CuZn@TrEG NPs was improved (>70% up to 25 and 20 μg/mL, respectively). The different effect of CuO@PEG and CuZn@TrEG NPs on different cell types could be attributed to the ability of most mononuclear cells to phagocyte extracellular NPs. Considering the ionic release of the tested NPs, it seems that there is a correlation between the quantity of released ions and the biocompatibility of NPs. Both CuO@PEG and CuZn@TrEG exerted enhanced ionic release, while the ionic release of ZnO@PEG NPs was negligible.…”
Section: Mic Determinationmentioning
confidence: 99%